2005
DOI: 10.1007/978-3-540-31985-6_19
|View full text |Cite
|
Sign up to set email alerts
|

CodeSurfer/x86—A Platform for Analyzing x86 Executables

Abstract: Abstract. CodeSurfer/x86 is a prototype system for analyzing x86 executables. It uses a static-analysis algorithm called value-set analysis (VSA) to recover intermediate representations that are similar to those that a compiler creates for a program written in a high-level language. A major challenge in building an analysis tool for executables is in providing useful information about operations involving memory. This is difficult when symbol-table and debugging information is absent or untrusted. CodeSurfer/x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 10 publications
(10 reference statements)
0
78
0
Order By: Relevance
“…This typically manifests itself in either false positives (Johnson et al 2013) or false negatives (Engler and Musuvathi 2004) depending on the analysis model. In the area of binary analysis even the most powerful static technique has problems handling even the most basic aggregate arrays (Balakrishnan et al 2005). On the other hand dynamic analysis is inherently context sensitive since it reasons about a concrete execution path.…”
Section: Static Versus Dynamic Analysismentioning
confidence: 99%
“…This typically manifests itself in either false positives (Johnson et al 2013) or false negatives (Engler and Musuvathi 2004) depending on the analysis model. In the area of binary analysis even the most powerful static technique has problems handling even the most basic aggregate arrays (Balakrishnan et al 2005). On the other hand dynamic analysis is inherently context sensitive since it reasons about a concrete execution path.…”
Section: Static Versus Dynamic Analysismentioning
confidence: 99%
“…The CodeSurfer/x86 platform [6] is a proprietary platform for analyzing x86 programs. However, it was mainly designed for other applications such as slicing and does not provide some of the capabilities that we need.…”
Section: Related Workmentioning
confidence: 99%
“…This can be done by using the program-dependence graph (PDG) [14] instead of the controldependence graph. Balakrishnan et al [3] have demonstrated PDG construction for unannotated binaries, but the infrastructure to do this is not yet generally available.…”
Section: Design Alternativesmentioning
confidence: 99%